Czynniki stymulacji rozwoju rynku żywnościowego - Szwacka-Mokrzycka, Joanna; Miara, Adam (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2013)
Nowadays, marketable assets that determine the survival and development of enterprises are seen as the most important factors of development. This is particularly important in a highly saturated food market, where there is a strong need to find sources of constant competitive advantage. The purpose of the present article is to present the role and importance of marketable assets in stimulating the development of food industry companies. The paper begins with the presentation of the types of marketable assets and their role in building constant competitive advantage on the food market. In the second part the results of surveys conducted among enterprises of the food industry are presented; basing on these, the authors determine the companies’ priorities in the use of assets aiming at stimulating their development.